An improved counterbalance mechanism for A 3-DOF manipulator - Nguyen Minh Nhut; Phung Tri Cong (Journal of Technical Education Science, 2019)
This paper describes an improved counterbalance mechanism fitting with the common structure of industrial robot arms. We have also developed three degree of freedom (DOF) manipulator, whose structural design resembles industrial robots, aiming to apply Lead-through programming. To verify the mechanism, the robot was designed to carry a load of 3 kg at the end of effector, which is equivalent to a concentrated weight of last three DOFs having type of spherical wrists. As a result, the robot can remain any postures in its workspace even maximum horizontal reach without auxiliary actuators. Furthermore, the robot was handled successfully to be programmed by Lead-through method. In summary, the improvement is practical for general industrial robots.